The Pre-pandemic digital teaching. Starting point for an educational transformation in higher education - Gallego Trijueque, Sara; Matarín Rodríguez-Peral, Eva; Fondón Ludeña, Anabell (Journal of Learning Styles, 2020)
The digitization of societies shows how technology has become an engine of social transformation. This digitization has affected the classrooms and the educational system. The objective of this study is to inquire about the digital transformation that is taking place in the university environment; to know the digital tools that students use, both inside and outside the educational environment, and that can be implemented in the classroom, as well as their perception of technology-mediated learning. The information has been collected a few months before the pandemic situation of COVID-19, so it supposes a description of the university pedagogical reality, in which the weak points of the system are highlighted and it points to lines of work for a digital conversion What a response to this situation. This case study, carried out with a mixed methodology, shows that the frequent use, during the last decades, of digital tools in the classroom has not meant a comprehensive adaptation of higher education to new needs. This diagnosis points out lines of work in which to implement transformations that allow adapting teaching methodologies to these post-pandemic demands.